Risk factors and presence of antibodies to Brucella canis and smooth Brucella in dogs from the municipality of Araguaina, Tocantins, Brazil - Santana, Jordana Almeida; Seles Dorneles, Elaine Maria; Jayme, Valeria de Sa; Galvao, Samara da Rocha; Minharro, Silvia; Santos, Helcileia; Mathias, Luis Antonio [UNESP]; Dasso, Mauricio Gauterio; Heinemann, Marcos Bryan; Lage, Andrey Pereira (Universidade Estadual de Londrina (UEL), 2013)
Canine brucellosis is an infectious disease of worldwide distribution that can affect dogs, wild canids and man. It is caused by Brucella canis, but dogs can also be infected by smooth Brucella such as B. abortus and B. suis. Due to the increasing importance of dogs in our society, the scarcity of information about canine brucellosis in the country and its zoonotic character, the aims of the present study were (i) to conduct a survey on the infection by B. canis and smooth Brucella in dogs from the municipality of Araguaina, Tocantins, Brazil, and (ii) to evaluate the risk factors associated with these infections. Sera from 241 dogs were analyzed by agar gel immunodiffusion (AGID) to detect B. canis-antibodies, and Buffered Acidified Plate Antigen test (BAPA) and fluorescence polarization assay (FPA) to detect antibodies to smooth Brucella. From the 241 tested dogs, 132 reacted in the AGID and 128 reacted in the BAPA, but only two were positive in FPA. The seroprevalences of B. canis and smooth Brucella infections in dogs in Araguaina were 54.77% (95% CI: 48.25 to 61.17%) and 0.83% (95% CI: 0.10 to 2.97%), respectively. The analysis of risk factors showed associations between B. canis infection and vaccination against leptospirosis, and between B. canis infection and use of manufactured food. In conclusion, data from the present study showed a low prevalence of infection by smooth Brucella and a widespread and high prevalence of infection by B. canis in the city of Araguaina, Tocantins, Brazil.
Keywords: Canine brucelosis; epidemiology; agar-gel immunodiffusion; rose bengal test; fluorescence polarization assay; manufactured food; Vaccination